Beyond optical enhancement due to embedded metal nanoparticles in thin-film solar cells. (4th February 2016) - Mopurisetty, Sundara Murthy; Bajaj, Mohit; Ganguly, Swaroop
Abstract: Metal nanoparticles (MNPs) inside the active layer of thin-film solar cells are considered promising for light trapping, but they have also engendered concerns over their adverse impact on transport properties. Contrary to expectations, coupled optical and electrical simulations indicate that a purely electrical effect due to MNPs might result in an enhancement of the cell performance in addition to the gain from optical (plasmonic) effects. This electrical enhancement strongly depends on the MNP/semiconductor barrier height. On the other hand, the anticipated degradation due to trap states and surface recombination at the MNP/semiconductor interface may in fact be negligible.